2015
DOI: 10.1007/s10238-015-0357-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress levels are correlated with P15 and P16 gene promoter methylation in myelodysplastic syndrome patients

Abstract: Oxidative stress and abnormal DNA methylation have been implicated in some types of cancer, namely in myelodysplastic syndromes (MDS). Since both mechanisms are observed in MDS patients, we analyzed the correlation of intracellular levels of peroxides, superoxide anion, and glutathione (GSH), as well as ratios of peroxides/GSH and superoxide/GSH, with the methylation status of P15 and P16 gene promoters in bone marrow leukocytes from MDS patients. Compared to controls, these patients had lower GSH content, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 49 publications
3
21
0
Order By: Relevance
“… 24 emphasized the roles of CDKN2A/B products and related proteins in the regulation of β-cell mass, proliferation, and insulin secretory function, in addition to roles in other metabolic tissues. Furthermore, a relationship between CDKN2A/B and oxidative stress has been reported, which is highly correlated with the hypermethylation of CDKN2A/B 37 . Last, melatonin receptors have been found throughout the body in many tissues and it has been shown that melatonin inhibits insulin secretion by pancreatic β-cells.…”
Section: Discussionmentioning
confidence: 97%
“… 24 emphasized the roles of CDKN2A/B products and related proteins in the regulation of β-cell mass, proliferation, and insulin secretory function, in addition to roles in other metabolic tissues. Furthermore, a relationship between CDKN2A/B and oxidative stress has been reported, which is highly correlated with the hypermethylation of CDKN2A/B 37 . Last, melatonin receptors have been found throughout the body in many tissues and it has been shown that melatonin inhibits insulin secretion by pancreatic β-cells.…”
Section: Discussionmentioning
confidence: 97%
“…Related with this, the CDKN2B-AS1 and CDKN2A genes have not only been associated with POAG risk, but also with cancer and many other diseases that involve other tissues [ 64 , 65 , 66 , 67 ]. A possible relationship between the CDKN2B-AS1 / CDKN2A genes and oxidative stress has also been reported [ 68 ]. Regarding the TMCO1 gene, although its function seems less pleiotropic than the previous mentioned genes, there are works that relate it with several pathologies beyond those of its expression at the ocular level [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have implicated the oxidative stress and the hypermethylation of tumor suppressor genes in myelodysplastic syndrome and acute myeloid leukemia . These are common molecular mechanisms of myeloid neoplasias.…”
Section: Discussionmentioning
confidence: 99%